eg. the first loan is x, the second loan will be (9,000 - x)
First, we need to make an equation based on the problem
first interest + second interest = 492
5% of x + 6% of (9,000 - x) = 492
This is the equation
Second, solve the equation and find out the value of x (first loan)
0.05x + 0.06(9.000 - x) = 492
0.05x + 540 - 0.06x = 492
-0.01x + 540 = 492
-0.01x = 492 - 540
-0.01x = -48
x = -48/-0.01
x = 4,800
Third, find the second loan
9,000 - x
= 9,000 - 4,800
= 4,200
SUMMARY
The first loan that has interest of 5% is $4,800
The second loan that has interest of 6% is $4,200